Effectiveness and safety of denosumab on osteoporosis treatment in kidney transplant recipients - Jin Kyung Kwon; Yaerim Kim; Jin Hyuk Paek; Kyubok Jin; Seungyeup Han; Woo Yeong Park (Kidney Research and Clinical Practice, 2024)
Background Denosumab has been reported to improve bone mineral density (BMD), but the clinical impact of denosumab on osteoporosis in kidney transplant recipients (KTRs) remains controversial. Methods We analyzed 98 KTRs who used denosumab from 2018 to 2023. We investigated the change in BMD, laboratory findings, complications of denosumab, fracture risk assessment tool (FRAX) score, acute rejection within 1 year, and graft failure. Results Mean T-scores at 1 year after denosumab were significantly increased compared to mean T-scores pre-denosumab at the femur neck and spine area, respectively (-2.68 ± 0.68 vs. -2.81 ± 0.68, p < 0.001; -2.78 ± 0.96 vs. -3.21 ± 1.00, p < 0.001). The levels of calcium and phosphorus significantly decreased and those of vitamin D significantly increased at 1 year after denosumab, but there were no significant differences in parathyroid hormone, allograft function, and tacrolimus trough level. There were no recurrent fractures among 12 KTRs with a history of fracture, but three de novo fractures happened. Cardiovascular events occurred in three patients. Denosumab-induced hypocalcemia developed in eight patients, but severe hypocalcemia was observed in only one patient. Acute kidney injury did not happen. Urinary tract infection (UTI) occurred in 17 patients. Arthralgia occurred in four patients. FRAX score was significantly decreased after denosumab. Acute rejection within 1 year after denosumab developed in three patients. There was no graft failure. Conclusion The use of denosumab in KTRs is effective and safe for the treatment of osteoporosis and prevention of fracture, but it should be carefully monitored for complications, especially UTI.